Hard questions about soft power: a normative outlook at Russia's foreign policy - Makarychev, Andrey (2011)
Abstract: "Political interest in the concept of soft power, introduced to the international academic community a few decades ago, has recently been revitalized after a series of mass uprisings in a number of countries in North Africa and the Middle East. Arguably, the substantive issues raised by the Arab Spring cannot merely be reduced to either energy matters or to the application of military force by the anti-Gaddafi coalition. The essence of these developments is profoundly normative, and this is how they were perceived by most European analysts, who were keen to raise a set of value-laden questions: how effective has the EU been as a 'normative power' in its relations with neighboring autocratic regimes? Can other emerging powers - above all Turkey - become a better model for the Arab world? Can we expect the revolutionary virus to spread to other areas overwhelmed by authoritarian regimes, including the Caucasus and Central Asia? Against this dynamic background, it appears that the who